America City, Nemaha County - Hermesch, Jessica (Kansas State University, The Chapman Center for Rural Studies, 2014)
This study illustrates the lost town of America City in Nemaha County, Kansas, from its hopeful founding to its imminent decline. Originally built at what would become the southern edge of the county, America City’s history exhibits an almost perfect case study model of frontier settlements in Kansas. This study includes newspaper references, an early plat map of the town, and photographs of present-day America City.
Jessica Hermesch, “America City, Nemaha County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/132.
Keywords: America City; Parallel Road Trail; Red Vermillion Township; Kansas Territorial Legislature; Union Church